2021
DOI: 10.3389/fendo.2021.652639
|View full text |Cite
|
Sign up to set email alerts
|

Review: Obesity and COVID-19: A Detrimental Intersection

Abstract: Obesity has been recognized as an independent risk factor for critical illness and major severity in subjects with coronavirus disease 2019 (COVID-19). The role of fat distribution, particularly visceral fat (often linked to metabolic abnormalities), is still unclear. The adipose tissue represents a direct source of cytokines responsible for the pathological modifications occurring within adipose tissue in obese subjects. Adipokines are a crucial connection between metabolism and immune system: their dysregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…Recent literature data suggest that in addition to the well-established association between BMI-based obesity and severe COVID-19 outcome, the body fat distribution is also important; in particular, visceral adipose tissue and upper abdominal circumference have been proposed as simple tools for risk assessment in COVID-19 patients [ 122 , 123 , 124 , 125 ]. More recently, an interesting prospective multicenter study on hospitalized COVID-19 patients with respiratory failure showed that a larger neck circumference phenotype patient is more prone to have a negative outcome, a large neck being associated with an increased proinflammatory and prothrombotic status.…”
Section: Implications Of the Findings And Future Perspectivesmentioning
confidence: 99%
“…Recent literature data suggest that in addition to the well-established association between BMI-based obesity and severe COVID-19 outcome, the body fat distribution is also important; in particular, visceral adipose tissue and upper abdominal circumference have been proposed as simple tools for risk assessment in COVID-19 patients [ 122 , 123 , 124 , 125 ]. More recently, an interesting prospective multicenter study on hospitalized COVID-19 patients with respiratory failure showed that a larger neck circumference phenotype patient is more prone to have a negative outcome, a large neck being associated with an increased proinflammatory and prothrombotic status.…”
Section: Implications Of the Findings And Future Perspectivesmentioning
confidence: 99%
“…Population ageing and rise in obesity prevalence worldwide are the two biggest risk factors for non-communicable diseases, including degenerative diseases, sarcopenia, frailty, dementia, increased morbidity, and mortality putting a strain on finite healthcare resources (1)(2)(3)(4)(5). Physical inactivity during COVID-19 has further exacerbated the problem (6), and obesity has been recognized as the strongest risk for severe disease and mortality during COVID-19 (7). Elevated body mass index (BMI), waist circumference and/or waist hip ratio are often used to define obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the fat depot starts to decline with increasing ectopic fat deposition in the epicardium, bone marrow, muscle, liver and other sites leading to loss of lean mass and organ dysfunction (21). Adipose tissue is pro-inflammatory, and obesity is associated with high baseline C-reactive protein, interleukin-6, low adiponectin and high leptin (7). Fat free mass includes body water, skeletal and smooth muscle mass, and bones.…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to induction of suppressor of cytokine signaling-3 (SOCS3) which, by inhibiting JAK/ STAT signaling, impairs IFN response [ 349 ]. Further, decreased TLR3 activation also leads to decreased IFN-1 production [ 350 ]. Increased expression of SOCS3 occurring in viral infection can also result in inhibition of leptin signaling and immune suppression by Treg cells [ 351 ].…”
Section: Why Is Obesity a Risk For Covid-19 ?—Pathways And Molecular ...mentioning
confidence: 99%